2015
DOI: 10.1016/j.marpol.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Permanent trawl fishery closures in the Mediterranean Sea: An effective management strategy?

Abstract: Since June 2010 the Italian government prohibited the trawling activity within three nautical miles from the coast or within the 50 m isobath. This decision was expected to have a great impact on trawl fishing activities, but at the moment no real assessment of the effects on catches and possible ecological implications has been undertaken. In order to fill this gap, an assessment on the North Western Adriatic Sea coast has been performed. Landings per Unit of Effort (kilograms per boat per day) for each trawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For its high level of productivity, mainly due to the presence of river estuaries, the Northern and Central Adriatic Sea (GSA17) is recognised to be intensively exploited by multi-gear and multispecific fisheries (Barausse et al, 2009;Pranovi et al, 2015;Fortibuoni et al, 2017;Russo et al, 2020).…”
Section: Study Area and Fishing Fleetsmentioning
confidence: 99%
See 2 more Smart Citations
“…For its high level of productivity, mainly due to the presence of river estuaries, the Northern and Central Adriatic Sea (GSA17) is recognised to be intensively exploited by multi-gear and multispecific fisheries (Barausse et al, 2009;Pranovi et al, 2015;Fortibuoni et al, 2017;Russo et al, 2020).…”
Section: Study Area and Fishing Fleetsmentioning
confidence: 99%
“…The GSA17 fleet is composed of industrial and small-scale fishing segments, flying the flag of Italy, Croatia, and Slovenia. The industrial one can be classified in demersal gears, that are bottom otter trawls (OTB, classified in large [LOTB, LOA >18 m] and small [SOTB, LOA <18 m]) and rapido trawl (RAP), a kind of beam trawl typical of the Italian Adriatic fleet and characterised by a serrated rigid mouth used to catch mainly flatfish and pectinids (Pranovi et al, 2015), and pelagic gears, which are midwater pair trawl (PTM, typical of the Italian fleet and called also volante) and purse seines (PS). The Small-Scale Fishery (SSF) is characterised by fishing vessels with an LOA under 12 m and limited tonnage (Lleonart and Maynou, 2003) that use passive gears, namely as gillnets, longlines, and traps.…”
Section: Study Area and Fishing Fleetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, trawling disrupts benthic community structure, selectively removing large-bodied target and non-target species, which are usually K-selected, resulting in a community dominated by relatively small r-selected species 13 , 14 . Given the significance of these impacts, a number of countries have implemented total or partial bans on bottom trawling within their territorial waters 15 , 16 or in the international waters they manage 17 . Nevertheless, a recent global review of ecosystem recovery following such bans 8 showed that most ecosystem recovery studies following trawl ban have been conducted in temperate waters, and only one of the 70 studies was conducted in the tropics 18 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Policymakers and managers consider seasonal fishery closure a useful intervention in addressing overexploitation and protecting species during their spawning season (Cinner et al, 2006;Arendse et al, 2007;Bavinck et al, 2008;Cohen et al, 2013;Colwell et al, 2019). Many different seasonal fishing closures have been implemented worldwide, such as restrictions on trawling by motorized and mechanized vessels (Morton, 2011;Barley Kincaid and Rose, 2014;Loring, 2017), shrimp trawling (Vivekanandan et al, 2010), and gill netting (Loring, 2017) for a short and defined period of time or permanently (Bavinck et al, 2008;Morton, 2011;Pranovi et al, 2015;Colwell et al, 2019;Amali Infantina et al, 2020) or for a single species (Vivekanandan et al, 2010;Oliver et al, 2015). These are widely recognized conservation and management measures that promote the safeguarding of species by restraining fishing and shielding the species during their spawning season (Hargraves, 2011;Cohen et al, 2013;Chimba and Musuka, 2014;Musiello-Fernandes et al, 2017;Narayanakumar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%